Production and Characterisation of Microfine Sized Palm Oil Fuel Ash (POFA) Originated from Bau, Lundu Palm Oil Mill - Raudhah, Ahmadi; Saiful, M.S.; Zawawi, D.F.; Sonia, Z A Rahman (EDP Sciences, 2016)
This paper investigates an effective and economical way for laboratory scale production of micro fine sized palm oil fuel ash (POFA) using an electric powder grinder. The raw POFA obtained from the palm oil mill is initially grinded by using Los Angeles abrasion machine, and then sieved using 150 μm sieve before it is burned in a furnace at 500°C. The burned POFA is then grinded using electric powder grinder to obtain the targeted micro fine sized. The physical, morphological and chemical properties of the micro fine sized POFA produced are analysed in the form of cement paste using Particle Size Analyzer (PSA), nitrogen sorption by using BET method, Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM) with Energy Dispersive Spectroscopy (EDS). The results show that 96% micro fine sized POFA is produced when using the optimum grinding process. The microstructural analyses of cement paste with 20% micro fine sized POFA replacement give the optimum results that contribute to higher compressive strength. The overall results of this research show that the optimum grinding process by using electric powder grinder is relevant and can be used as pioneering work in the concrete production industry